Evolution of structural characteristics of Nd0.7Ba0.3MnO3 perovskite manganite as a function of crystallite size - Kumar D.; Verma N.K.; Singh C.B.; Singh A.K. (My University, 2025)
Here, we present progression of structural characteristics with crystallite size of the nanocrystalline Nd0.7Ba0.3MnO3 perovskite manganite. The nanocrystalline samples of Nd0.7Ba0.3MnO3 have been synthesized by auto-combustion method. For structural analysis, X-ray diffraction patterns were recorded, which reveal that nano samples of Nd0.7Ba0.3MnO3 crystallize into orthorhombic crystal structure with space group Imma as confirmed by Rietveld refinement. The crystallite-size and lattice strain of the nano samples have been calculated using Williamson-Hall method. The unit cell volume increases while lattice strain decreases with increasing crystallite size. © 2018 Author(s).